2007
DOI: 10.1182/blood-2007-02-074450
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of transplantable porcine tumor cell lines derived from MHC- inbred miniature swine

Abstract: The lack of transplantable tumors has limited assessment of graft-versus-tumor effects following hematopoietic cell transplantation in clinically relevant largeanimal models. We describe the derivation and characterization of porcine tumor cell lines with initial efforts of tumor transplantation using immunocompromised mice and highly inbred sublines of Massachusetts General Hospital major histocompatibility complex (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…However, these sequences differ from eastern sequences by only one or two amino acids and of the seven new amino acid substitutions found among northwestern sequences only one substitution is located within a putative peptide interaction site. Rejection of transmissible tumours in experimental models can occur owing to only minor changes in MHC antigens or minor histocompatibility antigens (Sanford et al 1973;Cho et al 2007). However, given that Tasmanian devils with DFTD do not always have identical MHC Class I sequences to the tumour, the limited number of additional amino acid substitutions identified among northwestern devils may not affect DFTD transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, these sequences differ from eastern sequences by only one or two amino acids and of the seven new amino acid substitutions found among northwestern sequences only one substitution is located within a putative peptide interaction site. Rejection of transmissible tumours in experimental models can occur owing to only minor changes in MHC antigens or minor histocompatibility antigens (Sanford et al 1973;Cho et al 2007). However, given that Tasmanian devils with DFTD do not always have identical MHC Class I sequences to the tumour, the limited number of additional amino acid substitutions identified among northwestern devils may not affect DFTD transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore a CD80- or CD86-expressing porcine antigen presenting cell line is required in order to assess the binding function of the soluble porcine CTLA-4 in vitro . Using FACS analysis with hamster anti-mouse CD80 mAb (clone 16-10A1) (BioLegend, Cat#104703) a porcine CD80-expressing B-cell lymphoma cell line (LCL13271-5E4) was successfully screened from our available potential porcine B-cell lymphoma cell lines [10]. As shown in Figure 5A and 5B, FACS binding analysis demonstrated that both biotinylated glycosylated and non- N -glycosylated soluble porcine CTLA-4 bound to the porcine CD80-expressing B-cell lymphoma cell line LCL13271-5E4 in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Porcine B-cell lymphoma tumor cell lines available in our laboratory [10] were cultured in T75 culture flasks (Corning, Cat# 10-126-31) with 1x RPMI 1640 media supplemented with 12% fetal bovine serum, 10 mM hepes ( N -2-hydroxyethylpiperazine-N-2-ethanesulfonic acid), 1x nonessential amino acids, 1mM sodium pyruvate, 2 mM glutamine, and 2.5 × 10 −5 M 2-mercaptoethanol. Cultures were incubated at 37°C with 5% CO 2 until a cell density of 1.0 × 10 6 cells/mL was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Porcine IL-2 fusion toxins were eluted using 40 mM imidazole. Western blot analysis, FACS analysis, FACS competition/blocking analysis and K D determination were all performed as previously described (Peraino et al, 2012) using LCL13271 cells (Cho et al, 2007). The Ontak ® -like monovalent human IL-2 fusion toxin (DT390-hIL-2) used as a control for our in vitro assay was constructed, expressed and purified exactly same as the monovalent porcine IL-2 fusion toxin.…”
Section: Methodsmentioning
confidence: 99%